PENGARUH KADAR AKTIVATOR 0,43 DAN RASIO SS/SH (2,0-3,0) PADA BETON GEOPOLIMER DENGAN BAHAN DASAR FLY ASH TERHADAP KUAT TEKAN - Budi, Agus Setiya; Setiono, Setiono; Akbar, Masdihar (Universitas Teuku Umar, 2024)
AbstractAn alternative to reduce carbon dioxide emissions is to replace cement with fly ash in geopolymer concrete. Geopolymer concrete is an alternative to reducing carbon dioxide emissions by replacing 100% cement with other materials such as fly ash and a combination of SS (sodium silicate) and SH (sodium hydroxide). This research can provide knowledge on how the slump and compressive strength of geopolymer concrete produced with the use of alkali activator: fly ash ratio of 0.43. The test object consisted of 5 samples of size 15 cm x 30 cm with SS/SH variation of 2.0; 2.5; 3.0. The workability test was conducted using the slump test, while the compressive strength was conducted using a compression testing machine. The slump test results of variations 2.0; 2.5; 3.0 were 18.5 cm, 18 cm, and 17 cm, respectively. In addition, the compressive strength values were 40.78 MPa; 44.97 MPa; 45.80 MPa, respectively. Keywords—alkali activator, geopolymer concrete, fly ash, compressive strength.